Upaya Penanganan Tindakan Bullying melalui Penerapan Pendidikan Karakter pada Siswa Kelas VII di MTs Al-Ikhlas Proklamasi Karawang - Nenden Octaviani; Astuti Darmiyanti; Muhamad Taufik Bintang Kejora (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Currently, character education is in the spotlight because of the many moral declines. Character education has become a model of education offered to overcome the moral problems of children in Indonesia. This is related to the increase in juvenile delinquency which causes moral decline in children, one of which is bullying. In this regard, this study aims to help overcome the problem of bullying through the application of character education. The approach used in this study is a descriptive qualitative approach. The process of collecting data in this research is to use the method of interviews, observation and documentation. Then the data were analyzed using descriptive analysis techniques, namely starting from data reduction, data presentation and drawing conclusions. The results of this study indicate that there are forms of bullying that occur at MTs Al-Ikhlas Proklamasi Karawang. The forms of bullying that occurred at MTs Al-Ikhlas Proklamasi Karawang were divided into two forms. Namely verbal forms of bullying, such as mocking, shouting, and making fun of calls. While bullying is a social form of exclusion. In the process of implementing character education values ​​at MTs Al-Ikhlas Proklamasi Karawang, it is carried out using three strategies, namely by integrating character values ​​in the teaching and learning process, by habituation and through the culture of the school environment. Efforts made by MTs Al-Ikhlas Proklamasi Karawang in handling this bullying act are in the form of advising and applying the values ​​of character education, but if the student still does not change, the school will call the parents of the students involved in the bullying. Based on the results of this study, the authors hope that the school will pay more attention to the behavior of its students and always instill the values ​​of character education in students